Arthroscopic Assisted Treatment of Combined Trapezium and Bennett Fracture-Dislocation. Issue 1 (23rd March 2023) - Tandioy-Delgado, Fabio Andrés; Marcovici, Lucian Lior; Luchetti, Riccardo; Atzei, Andrea
Abstract : Trapezium fractures are unusual; however, they represent the third most frequent fracture of the carpal bones. As they usually follow a high-energy trauma, they are associated with distal radius, Bennett, or Rolando fractures in 80% of cases. Traditional treatment options include, closed reduction and percutaneous pinning, or open reduction and internal fixation. To minimize the additional surgical trauma, an arthroscopic technique has been developed for safe, minimally invasive management of complex injuries of the first carpo-metacarpal joint. Intra-articular dislocated fracture fragments are reduced under direct visualization and fixed through small incisions. Limiting additional surgical damage on the carpo-metacarpal joint ligaments, capsule, and other soft tissues around the fracture preserves the blood supply to fracture fragments and also the proprioceptive system, which is key for the dynamic stability of such a hypermobile joint. This report confirms that the procedure is feasible, and a complete functional recovery can be expected with reduced postoperative rehabilitation.